The interesting interplay between interneurons and adult hippocampal neurogenesis - Masiulis, Irene (2011)
Adult neurogenesis is a unique form of plasticity found in the hippocampus, a brain region key to learning and memory formation. While many external stimuli are known to modulate the generation of new neurons in the hippocampus, little is known about the local circuitry mechanisms that regulate the process of adult neurogenesis. The neurogenic niche in the hippocampus is highly complex and consists of a heterogeneous population of cells including interneurons. Because interneurons are already highly integrated into the hippocampal circuitry, they are in a prime position to influence the proliferation, survival, and maturation of adult-generated cells in the dentate gyrus. Here we review the current state of our understanding on the interplay between interneurons and adult hippocampal neurogenesis. We focus on activity- and signaling-dependent mechanisms, as well as research on human diseases that could provide better insight into how interneurons in general might add to our comprehension of the regulation and function of adult hippocampal neurogenesis.